Gambaran Klinis dan Elektrofisiologi Pasien dengan Sindrom Guillain-Barré di RSUD dr. Zainoel Abidin Periode Januari-Mei 2025 - Warzukni (PERDOSNI, 2025)
Introduction: Guillain-Barré Syndrome (GBS) is an acute peripheral polyneuropathy characterized by progressive muscle weakness and areflexia. Clinical manifestations and electrophysiological findings, such as those obtained Nerve Conduction Study (NCS) are essential for diagnosis, classification of subtypes, and determining prognosis. Objective: To describe the spectrum and electrophysiological characteristics of adult GBS patients treated at Neurology Department in dr. Zainoel Abidin General Hospital (RSUDZA), Banda Aceh, during the period of January to May 2025. Method: This was a descriptive observational study using medical record data of patients diagnosed with GBS who underwent nerve conduction study examinations. The data collected included demographic characteristics and electrophysiological patterns. Results: In this study, 16 patients diagnosed with Guillain-Barré Syndrome (GBS) were admitted to RSUDZA between January and May 2025, with 8 males (50.0%) and 8 females 50.0%). The patients' ages ranged from 13 to 71 years, with an average of 38.8 years. The majority were in the 41-50 age group (37.5%). All patients experienced weakness in all four limbs and reduced reflexes, except for 1 patient (6.3%) with normal reflexes. Out of 16 patients, 18.8% had a history of diarrhea, and 18.8% had respiratory infections. Electrophysiological results showed 84.6% had AMAN, and 7.7% had AMSAN, 7.7% had Miller-Fisher Syndrome and no patients were diagnosed with AIDP. Discussion: GBS patients at RSUDZA during the January–May 2025 period predominantly exhibited classic clinical features such as symmetrical weakness and areflexia, with axonal neuropathy being the most common electrophysiological subtype. Clinical assessment combined with nerve conduction study plays a crucial role in diagnosing GBS. Keywords: Guillain-Barré Syndrome, Nerve Conduction Study, polyneuropathy, RSUDZA